Analisis Rasio Keuangan Perbankan yang Mempengaruhi Non Performing Loan (NPL) Periode 2015-2017 (Studi Kasus Pada Bank Umum Konvensional yang Terdaftar di Bursa Efek Indonesia) - Faisal Amir; Anis Dwiastanti; Ida Nuryana (Jurnal Riset Mahasiswa Manajemen, 2019)
This studyto determine the effect of financial ratios on non-performing loans (NPLs) on conventional commercial banks listed on the Indonesia Stock Exchange in the 2015-2017 period. This type of research is quantitative research. The population in this study were all conventional commercial banks listed on the Indonesia Stock Exchange from 2015-2017 totaling 42 banks. Sampling was done by purposive sampling method. According to Sugiyono (2010) purposive sampling is a sample taken based on certain considerations or criteria. The number of samples to be used in this study were 25 conventional commercial banks listed on the Indonesia Stock Exchange in the 2015-2017 period. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that simultaneously CAR, LDR, LAR, and BOPO variables have a significant effect on Non-Performing Loans (NPL). While partially the Capital Adequacy Ratio (CAR) does not affect the Non Performing Loan (NPL), the Loan to Deposit Ratio (LDR) has a negative and significant effect on the Non Performing Loan (NPL), the Loan to Assets Ratio (LAR) has no effect on the Non Performing Loans (NPL), and Operating Expenses and Operating Income (BOPO) have a significant and positive effect on Non-Performing Loans (NPL).